Idiopathic Granulomatous Mastitis: A Case Series Study - Akter, Shahana; Sharif, Shah Muhammad (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Idiopathic granulomatous mastitis (IGM) is a rare, benign, inflammatory breast disorder that often mimics breast carcinoma or breast abscesses, leading to significant diagnostic and therapeutic challenges. A clear understanding of its presentation and optimal management is vital to prevent misdiagnosis and recurrence. Methods: This was a retrospective case-series study conducted in the Department of General Surgery at Shahabuddin Medical College Hospital (SMCH), Dhaka, over a three-year period (October 2021– September 2024). A total of 11 female patients (aged 20–45 years) with histopathologically confirmed IGM (non-caseating granulomas, and absence of infectious etiologies) were included. Patient demographics, clinical presentation, diagnostic characteristics, and treatment outcomes were analyzed. Results: The cohort consisted primarily of young, premenopausal women, with variable presentations ranging from solid, painless masses (mimicking fibroadenoma/carcinoma) to severe, recurrent suppurative disease characterized by chronic abscesses and multiple discharging sinuses. Initial misdiagnosis (fibroadenoma, standard abscess) was common. Rigorous exclusion of tuberculous mastitis (TM) was essential, highlighted by one included case of confirmed TM (Case 6). Conservative medical management with antibiotics and steroids frequently resulted in insufficient improvement or recurrence. In contrast, wide local excision (WLE) was successfully employed in cases of chronic, recurrent, or fistulating IGM (7 out of 12 cases), yielding durable, symptom-free recovery on follow-up. Conclusion: Idiopathic Granulomatous Mastitis (IGM) presents a heterogeneous clinical and diagnostic challenge. While conservative treatment may be considered for uncomplicated cases, this series strongly suggests that wide local excision should be prioritized for complicated, recurrent, or fistulating IGM to achieve superior and sustained resolution, particularly in endemic areas where exclusion of tuberculous mastitis is paramount. Ibrahim Card Med J 2024; 14 (2): 45-53